Molecular comparison of delta beta-thalassemia and hereditary persistence of fetal hemoglobin DNAs: evidence of a regulatory area? - Sergio Ottolenghi; Barbára Giglioni; Roberto Taramelli; Paola Comi; U Mazza; Giuseppe Saglio; Clara Camaschella; Paola Izzo; Antonio Cao; R. Galanello; E Gimferrer; Montserrat Baiget; et al. (1982)
The hematological phenotypes of several Mediterranean patients with delta beta-thalassemia and hereditary persistence of fetal hemoglobin have been characterized. Although clinical and hematological characteristics are essentially superimposable in all heterozygous delta beta-thalassemics, these patients show typical G gamma/A gamma ratios in their Hb F, ranging from approximately 0.07 in Sardinian to approximately 0.15 in Sicilian and approximately 0.35 in Spanish patients. A gamma Sardinian-(isoleucine-75 leads to threonine) is found in Spanish patients and accounts for all of the A gamma production in heterozygotes, indicating that persistent production of gamma chains occurs cis to the delta beta-thalassemia gene. The molecular heterogeneity of these conditions is demonstrated by restriction enzyme mapping of DNA; Sicilian and Calabrian patients show a deletion starting from the delta-globin intron and extending several kilobases 3' to the beta-globin gene; in Spanish patients the deletion starts approximately 2-3 kilobases 5' to the delta-globin gene and extends well beyond the beta-globin gene. Comparison of these deletions with previously described ones in Negro and in a new Southern Italian case of hereditary persistence of fetal hemoglobin suggests that the deletion of a region centered at a cluster of repetitive sequences approximately 3.5 kilobases 5' to the delta-globin gene may be critical for the persistent expression of high levels of gamma-globin in hereditary persistence of fetal hemoglobin compared to delta beta-thalassemia. The concept that the deletion or mutation of specific areas (rather than nonspecific changes brought about by large deletions in the globin cluster) is important in determining the persistent expression of gamma-globin genes is supported by the finding of a nondeletion type of delta beta-thalassemia in Sardinians.